Oriental Institute Museum Notes. 8: Achaemenid Jewelry in the Oriental Institute - Kantor, H. J.
Introduction — Necklace — Brasteates and Roundels with Loopes for Attachment — Striding Lion and Griffin Heads — Roundel with Winged Lion — Roundels with Addorsed Lions — The Ahuramazda Roundel — Provenience and Date — Conclusion.